Johann Sebastian Bach's Christmas oratorio - Rathey, Markus,Bach, Johann Sebastian (Oxford University Press, 2016)
In the last decades of the 17th century, the feast of Christmas in Lutheran Germany underwent a major transformation. Theologians and local governments waged an early modern
Literaturverzeichnis: Seite 391-407
Keywords: Weihnachts-Oratorium; Bach; Johann Sebastian